Feasibility of Apatinib in Radioiodine-Refractory Differentiated Thyroid Carcinoma - Du, Wei; Shi, Xiangyu; Fang, Qigen; Zhang, Xu; Liu, Shanting (Frontiers in Endocrinology, 2022)
Objectives: To describe our experience of using apatinib for radioiodine refractory differentiated thyroid carcinoma (RAIR-DTC) treatment. Methods: Forty-seven patients undergoing apatinib treatment for RAIR-DTC were prospectively enrolled in this study. The study endpoints were objective response rate (ORR), disease control rate (DCR), progression free survival (PFS), overall survival (OS), and rate of adverse events. Results: No patients achieved complete response: 36 (76.6%) and 8 (17.0%) patients achieved partial response and stable disease, respectively. The ORR and DCR were 76.6% and 93.6%, respectively. The median PFS was 18 months and the median OS was 59 months. A total of 91 adverse events occurred, of which 21 were graded as grade 3 or higher. There were no drug-related deaths. Conclusions: Apatinib has distinct anti-RAIR-DTC efficacy, in terms of ORR, PFS, and OS, and has a favorable safety profile. It is a feasible treatment option for RAIR-DTC.